1992
DOI: 10.1099/00221287-138-12-2575
|View full text |Cite
|
Sign up to set email alerts
|

A developmental mutation (npfL1) resulting in cell death in Physarum polycephalum

Abstract: In Physarum, microscopic uninucleate amoebae develop into macroscopic multinucleate plasmodia. In the mutant strain, RA614, plasmodium development is blocked. RA614 carries a recessive mutation (npfzl) in a gene that functions in sexual as well as apogamic development. In npfz+ apogamic development, binucleate cells arise from uninucleate cells by mitosis without cytokinesis at the end of an extended cell cycle. In npfzl cultures, apogamic development became abnormal at the end of the extended cell cycle. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The mutant strain C L 6 l l l carries the recessive npfA1 mutation; this strain was isolated from thegadAh strain CL following mutagenesis of amoebae and enrichment for cells that failed to form plasmodia (Anderson & Dee, 1977 strains carrying different m a t A alleles, indicating that the npfA+ allele was not essential for sexual development. The npfA locus is unlinked to the developmental loci n p p , npfz and matA (Anderson & Dee, 1977;Bailey et al, 1992a). Our analyses showed that npfA was also unlinked to npfG, npfx and npfM (data not shown; P > 0.05, x2 tests).…”
Section: Mutations Causing Early Blocks In Plasmodium Developmentmentioning
confidence: 61%
“…The mutant strain C L 6 l l l carries the recessive npfA1 mutation; this strain was isolated from thegadAh strain CL following mutagenesis of amoebae and enrichment for cells that failed to form plasmodia (Anderson & Dee, 1977 strains carrying different m a t A alleles, indicating that the npfA+ allele was not essential for sexual development. The npfA locus is unlinked to the developmental loci n p p , npfz and matA (Anderson & Dee, 1977;Bailey et al, 1992a). Our analyses showed that npfA was also unlinked to npfG, npfx and npfM (data not shown; P > 0.05, x2 tests).…”
Section: Mutations Causing Early Blocks In Plasmodium Developmentmentioning
confidence: 61%
“…The plates were incubated at 24°C for 48 h to facilitate hatching of amoebae from cysts and subsequently at 30°C to allow amoebal growth while suppressing the unwanted formation of haploid plasmodia by apogamic development (Bailey et al . , ; Bailey ). After several days at 30°C, amoebal colonies became visible.…”
Section: Methodsmentioning
confidence: 99%
“…100 lL of the diluted amoebal cyst suspension were mixed on a plate with 100 lL of a standardized formalin-killed E. coli suspension that served as a food source for the amoebae (FKB; [Dee 1986]) and the droplet was spread evenly over a DSPB agar plate (diluted semidefined phosphate buffered medium; [Anderson et al 1997]) by streaking with the conical tip of a 10-mL glass pipette. The plates were incubated at 24°C for 48 h to facilitate hatching of amoebae from cysts and subsequently at 30°C to allow amoebal growth while suppressing the unwanted formation of haploid plasmodia by apogamic development (Bailey et al 1987(Bailey et al , 1992Bailey 1995). After several days at 30°C, amoebal colonies became visible.…”
Section: Methodsmentioning
confidence: 99%
“…l a ; Bailey et al, 1992;Solnica-Krezel e t al., 1995). This is consistent with previous studies implicating the second half of this cell cycle as a crucial one for development, when many alterations in gene expression and cellular organization begin (e.g.…”
Section: Mutations Causing Later Blocks In Plasmodium Developmentmentioning
confidence: 99%